Analisis Kesenjangan Ekspektasi dan Realita Hubungan Mahasiswa dan Mitra Magang dalam Program Magang Merdeka Belajar - Ema Isnaini Agustin; Masrukin Masrukin; Sulyana Dadan (Journal on Education, 2024)
The relationship between internship partners and students is an important factor in the success of the internship program. However, there is one problem that can occur in the relationship between internship partners and students, namely a gap in the relationship that can occur due to differences in expectations between internship partners and students and vice versa. This research aims to find out strategies that can be implemented to overcome the gap in the relationship between internship partners and students of the Merdeka Belajar Kampus Merdeka Internship Program. By using the literature study method. The results of this research are; Relationship gaps that occur in the internship program above include; communication is not optimal, SOPs for apprenticeship procedures, facilities for apprenticeship partners are inadequate, differences in communication methods between apprenticeship partners and students, apprenticeship partners do not have a position size and target time for work that must be carried out by students, there is no KPI transparency. Strategies that can be used to overcome these problems are open communication regarding work expectations and limitations, understanding job duties and responsibilities, internship partners should develop clear guidelines regarding work and expectations for the quality of student performance, and provide opportunities for students to convey aspirations and channel his interests and skills. This analysis can help identify problems in internship programs and find strategies to overcome these problems, and can be a reference in developing better policies to support internship programs in the future.